Peran Arbitrase dalam Resolusi Sengketa Internasional: Studi Kasus Sengketa Laut Tiongkok Selatan - Mustika, Tasya Gina; Azzahra, Salsya Tasyuah; Putra, Risyan Satria (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to find out how the arbitration line could settle south China's sea dispute. The study USES a normative-law study method, including a constitutional approach, a case approach, and a historical approach. Data collected and processed is viewed as secondary; The collection of primary and secondary legal materials is done by literature; Thereafter, the data is systematized and analyzed through descriptive methods. The results of this study explain south China sea disputes raised by the Philippines, which feel that they have a right to the region. The Philippines brought their conflict with the country of China in the south China sea into the international arbitration system. The Philippines claims that the coral reef environment was damaged by China's action to build an artificial island.